20 years experience with appendicovesicostomy in paediatric patients: Complications and their re‐interventions. Issue 5 (27th May 2016) - Reuvers, Sarah H.M.; van den Hoek, Joop; Blok, Bertil F.M.; de Oliveira Barbosa, Telma C.; Wolffenbuttel, Katja P.; Scheepe, Jeroen R.
Abstract : Aims: To evaluate the long‐term outcome of appendicovesicostomies and to present the frequency and timing of complications needing re‐intervention. Methods: In this retrospective study we included patients in whom an appendicovesicostomy was created at our institution between 1993 and 2011. Patients with a follow‐up less than 1 year were excluded. Patient characteristics and conduit‐related complications requiring re‐intervention were collected. Results: One hundred and twenty‐eight patients were included with mean age at initial surgery of 10.1 ± 3.9 years. Two thirds of the children had underlying neurogenic disease. The mean follow‐up was 10.1 ± 4.8 years. All but one patient continued to use the catheterizable channel. Re‐intervention for conduit‐related complications was necessary in 32.0% of the patients. A second, third, and fourth re‐intervention was required in respectively 10.9%, 2.3%, and 1.6%. The commonest complications were cutaneous/fascial stenosis in 14.8%, stenosis at conduit‐bladder level in 9.4%, and stomal incontinence in 6.3% of the patients. The most performed re‐interventions were stoma revision (in 16.4% of the patients), conduit revision (10.2%), and dilatation of a stenotic tract (4.7%). 63.3% of the re‐interventions was superficial and/or endoscopic. The peak incidence of re‐interventions was in the 1st year after conduit construction and decreased yearly. Conclusions: Our study gives an overview of patients and their conduits developing from prepubertal children to young adults. During a mean follow‐up of 10.1 years, roughly one third of the patients needed a re‐intervention. We conclude that an appendicovesicostomy is an effective and durable treatment for whom transurethral clean intermittent catheterization is not feasible. Neurourol. Urodynam. 36:1325–1329, 2017 . © 2016 Wiley Periodicals, Inc.